“Sem Pressão”: application with guidelines for identification, staging and prevention of pressure injuries - Siqueira Campos, Rosana; Blanes, Leila; Nicodemo, Denise; Masako Ferreira , Lydia (Estima – Brazilian Journal of Enterostomal Therapy, 2020)
Objective: develop an application with guidance on the identification, staging and prevention of pressure injuries in adults. Method: the descriptive method used started with the search for applications in the area of pressure injuries on the Google © and Apple © platforms. Afterwards, the content was developed, based mainly on the recommendations of the National Pressure Injury Advisory Panel. A prototype was created at www.fábricadeaplicativos.com.br and sent for evaluation of form and content. Six health professionals completed a questionnaire evaluating the application and two of them suggested changes. The application was adequate to the suggestions and reassessed by three stomatherapist nurses who did not suggest changes. Results: the application was developed on the “application factory” website and named “Sem Pressão” (No Pressure), with seven tabs. Conclusion: the application was created with guidelines on identification, staging and prevention of pressure injuries in adults, and made available for free download.